Spectroscopic study of the C(3)1Σ+ ← X1Σ+ and c(2)3Σ+ ← X1Σ+ transitions in KCs molecule. (January 2018) - Szczepkowski, Jacek; Grochola, Anna; Kowalczyk, Pawel; Jastrzebski, Wlodzimierz
Highlights: The C 1 Σ + ← X 1 Σ + and c 3 Σ + ← X 1 Σ + band systems of KCs observed by polarisation labelling spectroscopy. The pointwise potential energy curve of the C 1 Σ + state constructed from experimental data. The pointwise potential energy curve of the c 3 Σ + state constructed from experimental data. The results compared with the theoretical predictions. Abstract: We present an experimental investigation of the C(3) 1 Σ + and c(2) 3 Σ + states of KCs using two-colour polarisation labelling spectroscopy (PLS) technique. Pointwise potential energy curves are generated for both states using the inverted perturbation approach (IPA) method. The experimental pointwise potentials and molecular constants Te, ωe and Re are compared with theoretical calculations.